Integrated Translatomics with Proteomics to Identify Novel Iron–Transporting Proteins in Streptococcus pneumoniae - Yang, Xiao-Yan; He, Ke; Du, Gaofei; Wu, Xiaohui; Yu, Guangchuang; Pan, Yunlong; Zhang, Gong; Sun, Xuesong; He, Qing-Yu (Frontiers in Microbiology, 2016)
Streptococcus pneumoniae (S. pneumoniae) is a major human pathogen causing morbidity and mortality worldwide. Efficiently acquiring iron from the environment is critical for S. pneumoniae to sustain growth and cause infection. There are only three known iron-uptake systems in Streptococcal species responsible for iron acquisition from the host, including ABC transporters PiaABC, PiuABC and PitABC. Besides, no other iron-transporting system has been suggested. In this work, we employed our newly established translating mRNA analysis integrated with proteomics to evaluate the possible existence of novel iron transporters in the bacterium. We simultaneously deleted the iron-binding protein genes of the three iron-uptake systems to construct a piaA/piuA/pitA triple mutant (Tri-Mut) of S. pneumoniae D39, in which genes and proteins related to iron transport should be regulated in response to the deletion. With ribosome associated mRNA sequencing-based translatomics focusing on translating mRNA and iTRAQ quantitative proteomics based on the covalent labeling of peptides with tags of varying mass, we indeed observed a large number of genes and proteins representing various coordinated biological pathways with significantly altered expression levels in the Tri-Mut mutant. Highlighted in this observation is the identification of several new potential iron-uptake ABC transporters participating in iron metabolism of Streptococcus. In particular, putative protein SPD_1609 in operon 804 was verified to be a novel iron-binding protein with similar function to PitA in S. pneumoniae. These data derived from the integrative translatomics and proteomics analyses provided rich information and insightful clues for further investigations on iron-transporting mechanism in bacteria and the interplay between Streptococcal iron availability and the biological metabolic pathways.